Effectiveness of a one-day laparoscopic suture course. (3rd October 2019) - Peker, Nuri; Biler, Alper; Hortu, İsmet; Şendağ, Fatih
Abstract: We aimed to determine the effectiveness of a one-day course on laparoscopic suturing skills development by performing a prospective study with obstetrics and gynaecology specialists. The course consisted of a theoretical portion describing the suturing technique basics and a practical portion consisting of box trainer suturing. Before and after the course, each trainee was given 10 min to introduce the suture material into the abdomen, properly position the needle using a needle holder, pass the suture through premarked points on the silicone pads and tie an intracorporeal knot. The procedures were video recorded and evaluated after the course. The results showed that there were statistically significant reductions in the needle holding, suture passing and knot tying times after completing the course. Overall, the one-day course was an effective training programme for improving a surgeon's laparoscopic suturing skills. IMPACT STATEMENT: What is already known on this subject? Currently, many countries have centres that provide laparoscopic training as part of the medical residency education. However, a standardised training programme has not been implemented worldwide. What do the results of this study add? In this study, we pointed out the effectiveness of a one-day laparoscopic suturing course. A one-day suturing course is easy to implement, cheap and effective. What are the implications of these findings for clinical practice and/or further research? A one-day suturing course should be implemented worldwide, especially in those countries lacking sufficient financial resources to provide laparoscopic training as part of the medical residency programme.